Community‐Based Models to Improve Service Access: Rethinking Behavioral Health Crisis Response Pathways. (20th August 2020) - Sirkin, J.; Robinson, A.; Sparks, A.; Chapman, M.; Hoffman, C.; Sharp, C.
Abstract: Research Objective: We reviewed capacity in Massachusetts for crisis response and diversion (from arrest and emergency departments) to support the initiation of care for individuals who interact with law enforcement and are in behavioral health crisis. Our primary data collection assessed stakeholder perspectives on barriers and facilitators to implement community‐based diversion models, factors associated with timely access to behavioral health services, and recommendations for local policy improvements in Massachusetts. Study Design: Using purposive sampling, we conducted interviews with stakeholders responding to behavioral health crises in community settings (eg, Emergency Services Providers [ESPs], coresponders, law enforcement, first responders), emergency department physicians, peer recovery professionals, and housing experts. We also conducted two focus groups: 1) individuals and family members with lived experience and 2) an independent state Commission that included legislators, leaders of behavioral health agencies, law enforcement, courts, and advocacy organizations. Adapting Penchansky and Thomas's access framework, we characterized access dimensions—availability, accessibility, affordability, accommodation of individual needs, acceptability of care, and individual/family experience—as moderating diversion from arrest or emergency departments and the process of making timely connections to behavioral health services. Drawing from our conceptual framework, we developed semi‐structured interview and focus group guides. We analyzed detailed notes and transcripts using thematic analysis and collected informant feedback on preliminary findings (ie, member checking) with an independent Commission to develop a report for the Massachusetts Legislature in 2019. Population Studied: Law enforcement and behavioral health stakeholders (n = 10); focus groups with individuals and family members (n = 7); and Massachusetts Commissioners (n = 11). Principal Findings: We found that law enforcement agencies in MA implemented diverse strategies to support identification and response to behavioral health needs/crises, such as investing in specialized training, adopting coresponder models, establishing relationships with local providers, and initiating community outreach efforts. While local efforts have increased arrest diversion, stakeholders identified regulatory, transportation, resource, and data sharing barriers to diverting individuals from emergency departments. Focus group participants emphasized the importance of provider "fit" and choice across the care continuum; challenges navigating the system "labyrinth"; and lack of care continuity. Stakeholders noted a lack of viable alternatives for community‐based crisis services and timely behavioral health care, especially for individuals with complex medical needs, the elderly, children, and individuals who exhibit aggressive or violent behavior. Conclusions: Providing community‐based services, specifically for individuals in acute behavioral health crises, may help reduce both arrests and emergency department stays. Options to enhance diversion and access may include expanding specialized training, increasing embedded behavioral health care providers, expanding crisis stabilization beds, or implementing a restoration center with access to ESPs, social services, transportation, and other behavioral services. Consultation with key community stakeholders and coordination with existing models and services will be essential for implementation success. Implications for Policy or Practice: Policy makers are exploring alternatives to arrest or emergency departments for individuals with challenges accessing behavioral health care, including working to develop a community‐based restoration center model informed by these conclusions. The Commission's findings were submitted to the Massachusetts Legislature (June 2019); implementation of a restoration center is expected to begin in FY2021, pending Legislative approval. Primary Funding Source: Middlesex Sheriff's Office.